Combined testing of high-sensitivity Troponin T and Copeptin on presentation at prespecified cutoffs improves rapid rule-out of non-ST-segment elevation myocardial infarction - Giannitsis, Evangelos; Kehayova, Tzveta; Vafaie, Mehrshad; Katus, Hugo (Clinical chemistry, 2011)
Two recent clinical trials showed that adding copeptin to a conventional cardiac troponin assay improved diagnostic performance for patients with chest pain early after symptom onset. We prospectively tested whether copeptin adds information to that provided by a high-sensitivity cardiac troponin T (hscTnT) assay in the early evaluation of patients with suspected acute myocardial infarction, particularly non-ST-segment elevation myocardial infarction (non-STEMI).We enrolled 503 patients with suspected acute coronary syndrome and onset of chest pain occurring within the previous 12 h. Copeptin was measured on presentation, and hscTnT was measured serially at baseline and after 3 and 6 h. We used ROC curve analysis and likelihood ratio χ2 statistics for nested models. Diagnostic sensitivities, specificities, positive predictive values (PPVs), and negative predictive values (NPVs) were calculated for admission values of copeptin alone, hscTnT alone, and the combination of both markers.For ruling out non-STEMI (after excluding STEMI), an hscTnT concentration <14 ng/L (99th percentile) plus a copeptin concentration <14 pmol/L yielded a diagnostic sensitivity of 97.7% (95% CI, 91.9%-99.7%), an NPV of 99.03% (95% CI, 96.6%-99.9%), a diagnostic specificity of 55.9% (95% CI, 50.6%-61.0%), and a PPV of 34.4% (95% CI, 28.5%-40.7%). ROC curve analysis of the continuous biomarker values on admission demonstrated no added value of using this marker combination for ruling out non-STEMI when hscTnT was used as the standard for diagnosing non-STEMI.A strategy using copeptin with hscTnT at prespecified cutoffs improves the ruling out of non-STEMI, compared with using hscTnT alone; thus, this strategy could help to obviate a prolonged stay in the emergency department.